Venous Thromboembolism Post-allogeneic Hematopoietic Cell Transplant: Risk Factors, Incidence, and Outcomes - Granat, Lauren M.; Li, Hong; Ondeck, Mariah; Osantowski, Bennet; Peysin, Chana; Wilks, Mailey; Ferraro, Christina; Sobecks, Ronald; Angelini, Dana; Hamilton, Betty K. (Thrombosis and Haemostasis, 2024)
Background Venous thromboembolism (VTE) is a well-documented complication of both solid and hematologic malignancies, but there are fewer data on allogeneic hematopoietic cell transplant (HCT) recipients. Therefore, we studied the incidence, risk factors, and impact of VTE on post-HCT outcomes in a contemporary cohort.Methods We retrospectively reviewed patients who underwent allogeneic HCT between January 2014 and August 2019 to identify patients with post-HCT VTE. Patient, disease, and transplant-related risk factors for VTE were investigated using competing risk analysis.Results A total of 431 patients were included in this study. Median (interquartile range [IQR]) age in years was 59 (46–65) at transplant. The most common indication for transplant was acute myelogenous leukemia (49.4%). Within our cohort, 64 patients (14.8%) developed post-HCT VTE with a median (IQR) follow-up time of 24.6 (8.4–47.1) months. The cumulative incidence of VTE was 4.2% at 6 months, 9.0% at 12 months, 12.6% at 24 months, and 13.8% at 36 months. In multivariable analysis, older age (hazard ratio [HR] per 10-year increase: 1.36, 95% confidence interval [CI]: 1.09–1.70), history of VTE (HR: 1.95, 95% CI: 1.09–3.49), and grade 2–4 acute graft versus host disease (GVHD; HR: 1.75, 95% CI: 1.05–2.94) were independently associated with VTE. VTE was significantly associated with an increased risk of nonrelapse mortality (NRM; HR: 4.09, 95% CI: 2.47–6.74) and decreased overall survival (OS; HR: 2.19, 95% CI: 1.48–3.24).Conclusion VTE is an important complication after allogeneic HCT and is significantly associated with increased NRM and decreased OS. Older patients, those with prior VTE, and patients with acute GVHD are at increased risk for development of VTE after HCT.
Keywords: venous thromboembolism; deep vein thrombosis; malignancy